The Training of Portfolio-Based Learning Model to Develop The Democracy Value and The Students’ Critical Thinking Skill - Sulistyarini Sulistyarini; Bambang Budi Utomo; Rum Rosyid; Thomy Sastra Atmaja (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2019)
Pancasila and Citizenship Education (PPKn) Learning is a vehicle for democratic education. In the context of international discourse, PPKn learning in Indonesia is still included in the knowing democracy paradigm. While in other countries, it is already in the paradigm of building democracy. For this reason, PPKn learning needs to be facilitated so that it develops from the knowing democracy paradigm towards doing democracy. As a vehicle for the education and development of democratic citizens, the PPKn has three main functions, namely developing civic intelligence, fostering civic responsibility, and encouraging civic participation. The three competencies of citizens are in line with the three main components as a learning estuary for PPKn namely civic knowledge, civic skills and civic dispositions. PPKn learning can ideally equip students with sufficient knowledge and intellectual skills as well as provide practical experience to have competence and be able to participate effectively. For this reason, two things need attention in preparing PPKn learning in class, namely knowledge about learning materials and the use of learning methods/models. One learning model that is suitable to be applied in PPKn learning is portfolio-based because the superiority of this model in its application can develop democratic values and enhance students' critical thinking skills. However, discussions with several teachers obtained information that many of them did not understand the characteristics, advantages, and ways of implementing portfolio-based learning models on PPKn learning so that this model does not get the attention to be applied by teachers in learning PPKn. Community Service Activities were carried out on August 14, 2018, located at Sungai Pinyuh State Middle School 3, Mempawah Regency, and were attended by teachers from the MGMP PPKn SLTP level throughout the District of Mempawah. This community service activity has the goal of increasing teacher knowledge and understanding of planning, implementing, evaluating, and knowing the obstacles faced by teachers in applying portfolio-based PPKn learning to develop democratic values and critical thinking abilities of students. PKM activities carried out in the form/method of socialization. The result of this activity is an increase in the knowledge and understanding of PPKn teachers on the concepts and nature of portfolio learning models, the effectiveness of portfolio learning models to develop democratic values and critical thinking skills of students, the application of portfolio learning models in planning, implementing, and evaluating PPKn learning activities, and regarding various obstacles faced by PPKn teachers in applying the portfolio model.